From evidence to practice: Developing best practice guidelines for the delivery of activities to people living with moderate to advanced dementia using a pragmatic observational study. (July 2021) - Burke, Amanda; Jones, Andy; Hughes, Ryan; Player, Emily
The benefits of physical activities for those living with moderate to advanced dementia are well documented and include improved well-being and quality of life. What is less well known is how best to deliver such activities to make them meaningful for those taking part and, more generally, how to develop good practice guidance for working with this group. This article reports on an observational study of a physical activity programme in a residential care setting, Mobile Me, and on the process used to develop good practice guidance from it, which included input from a range of stakeholders. Learnings from this study conclude that changes in delivery and setting can contribute to a difference in the quality of the experience for participants and their levels of well-being during sessions. The findings from the study were consolidated into four themes for disseminating best practice: promoting the right atmosphere, environment, communication, and adaptations. These form part of a new multimedia best practice guide for delivering physical activities to those living with moderate to advanced dementia.